Путь к социалистическому предпринимательству - Аузан Александр Александрович (Политиздат, 1990)
Экземпляры: КХ (20100901) / Инвентарный номер: 960307 / Цена: 0.85 / Сис.шифр: 65.9(2) / Авт.знак: А 93 / ГРНТИ: 06.91 / ББК: 65.290